Improved tribological and thermal properties of lubricants by graphene based nano-additives. Issue 64 (21st June 2016) - Zin, V.; Barison, S.; Agresti, F.; Colla, L.; Pagura, C.; Fabrizio, M.
Abstract : Enhancing the tribological performance of lubricants with nanoparticle additives is a recent challenge. Addition of graphene based nanostructures in poly-alkylene glycol lubricant could significantly reduce friction and wear for compressors operating with CO2 refrigerant. Abstract : Enhancing the tribological performance of lubricants with nanoparticle additives is a recent challenge. The purpose of this study was to investigate the potential advantage of nanolubricants, a new class of advanced lubricants integrating nano-sized materials, to reduce friction and wear processes, in view of applications in compressors for refrigeration. An investigation of tribological and thermal properties of nanolubricants for vane-on-roller systems was carried out through ball-on-disk wear tests and thermal diffusivity photo-acoustic measurements from room temperature to 70 °C. Nanofluids containing different concentrations of graphene based nanostructures in oil were tested. Poly-alkylene glycol was selected as the oil, being a lubricant suitable for compressors operating with CO2 refrigerants. The suspensions resulted stable with time. The dispersed nanostructures played an important role in protecting surfaces against wear phenomena and in improving the friction properties and load carrying capability of raw oil. A maximum decrease of 18% for friction coefficient and over 70% for worn volume were estimated in boundary lubrication conditions, the most severe for tribological couplings. Finally, durability experiments and Stribeck tests confirmed the benefits produced by nano-additives in different lubrication regimes. Thermal investigation proved also the advantage of using nanolubricants in heat exchange properties in laminar flow conditions, e.g. during compressor power-up phases.